Grundtvig og Rødding Højskole - Lyby, Thorkild C. (Grundtvig-Studier, 1999)
Grundtvig and the Folk High School at Rødding By Thorkild Lyby In his book Vision og Virkeliggørelse (Vision and Fulfilment) Helge Grell has advanced the argument that Grundtvig had reservations about Rødding Folk High School, because it identified itself with the national struggle to such an extent that it did not fully practice Grundtvig’s original folk high school ideas. Against this view, the present article claims that it is impossible to disqualify Rødding as non-Grundtvigian. Following a discussion of what it takes for a folk high school to be called Grundtvigian, the article gives an outline of the history of Rødding up to the 1864 war which necessitated the transfer to Askov. The emphasis is on the attitudes of successive principals, predominantly, however, that of Christian Flor. Not only was he the driving force behind the establishment of the high school, but was its leader himself in 1845-46, and, as chairman of the Board of Governors and later the Committee, continued to exert a decisive influence on its affairs until it was closed down. It is argued that Flor was entirely a Grundtvig disciple, and that his only wish was to translate Grundtvig’s folk high school ideas into practice. It is true that Rødding was also intended as a school with a role to play in the national struggle, but in the circumstances this should not disqualify it as Grundtvigian since Grundtvig’s cultural struggle at the time must necessarily take the form of a national struggle. It is pointed out, moreover, that to the various principals the cultural view was more important than the national - if it is at all possible to distinguish between them. Another thing is that Grundtvig’s attitude to Rødding was ambiguous. He expressed delight at its establishment and welcomed it without reservations, and later too there is evidence of a sympathetic interest in it. On the other hand, there is also evidence of a strange indifference, as it appears for example from the fact that he never visited the school in spite of repeated invitations. No doubt, the reason is that he had envisaged his ideas about the education of the people to be realized through the great, state-supported high school at Sorø, which he had dreamed about since his youth, and which had very nearly become a reality in 1847-48. Only gradually did he realize that it was through the many smaller schools modelled on Rødding that his ideas were to attain their great importance.